HUBUNGAN PENILAIAN PRESTASI DENGAN KINERJA KARYAWAN SEBAGAI SUATU EVALUASI MANAJEMEN SDM (KASUS PT.SINAR SOSRO CABANG PEKANBARU) - Nova Lina Gultom; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PT. Sinar Sosro Pekanbaru Branch beam is packaged tea beveragecompany in Indonesia. The main activity of this company is mendistrubusikan andmarket products packaged tea beverage brands Sosro in Riau, West Sumatra andRiau Islands (KPW West Sumatra and Riau Islands). As a company sellingproducts Sosro beverage brands, the company would require the support of a goodquality of human resources. Good corporate HR can be seen from the employee'sability, or so-called employee performance.The efforts made by the company is focused on performance appraisal,performance appraisal which is a form of evaluation and creation of motivationthat comes from within the employee can improve the performance of theemployees themselves. High-performance employee owned, is a guarantee for thecompany's success in achieving its objectives.The purpose of this study was to analyze the relationship betweenperformance appraisal with employee performance. This study uses quantitativedesktiptif correlation technique in which the data were collected throughquestionnaires to 84 respondents. Spearman rank analysis was then performed onthe data obtained.The results of research and hypothesis testing shows that there is asignificant positive relationship between performance appraisal with theemployee's performance in PT.Sinar Sosro Pekanbaru Branch. Through theSpearman rank correlation analysis note that the assessment of achievement andperformance has coefficient value of 0.562, which in the interpretation of thevalue of the correlation coefficient indicates there is a relationship betweenperformance appraisals and employee performance is being categorized.Keywords: Performance Assessment, Performance, Motivation